Self-organized partitioning of dynamically localized proteins in bacterial cell division - Di Ventura, Barbara; Sourjik, Victor (Molecular systems biology, 2011)
How cells manage to get equal distribution of their structures and molecules at cell division is a crucial issue in biology. In principle, a feedback mechanism could always ensure equality by measuring and correcting the distribution in the progeny.
Gesehen am 10.05.2022